O desenvolvimento de habilidades metafonológicas em crianças de Educação Infantil ao final do ciclo da alfabetização - Araujo, Maria das Doris Moreira de (2020)
This research aimed to describe the metaphonological skills, of the phonemic and supraphonemic levels, of children in Early Childhood Education at the end of the literacy cycle. The choice of this study is justified by the interest and need to understand how these skills are developed, since there are no studies with this purpose in a more specific way. We base our research on Callou and Leite (2009), Mori (2004), Câmara Jr. (1996) and Leite (1990) to discuss the phonological component of the Portuguese language and to present the characteristics of such component. We took into account the grants from Matzenauer (2014; 2003), Abud (1987) and Silva (1981) to discuss the importance of phonology and linguistics for the teaching-learning process in the early school years. To present the concepts, literature and characteristics of phonological awareness, we followed authors such as Morais (2019 and 2012), Capovilla and Capovilla (2010), Correa (2001) and Cardoso-Martins (1995). And for the presentation of the relationship between phonological awareness and literacy, we take as a basis the readings of Castro (2013), Mcginnes (2006), Soares (2007) and Weisz (1999). We carried out a field research with sixty children from Infantil IV to the second year of Elementary School - fifteen children from each school year, from the Antônio Custódio de Azevedo school, located in the Aprazível district, in the municipality of Sobral, Ceará. We apply activities related to the phonemic and supraphonemic plan in order to ascertain the development of phonological awareness in this school period. The results were presented in two groups: phonemic and supraphonemic awareness in each school year. The first group listed eight aspects for analysis: identification and counting of letters, identification and counting of phonemes, identification of initial word phonemes, identification of final word phonemes, additions of initial phonemes, subtraction of initial phonemes, additions of final phonemes, and subtraction of final phonemes. In the supraphonemic consciousness group, we consider five categories of analysis: syllable identification, word unit identification, phrase identification and production, rhyme identification and word production. With this research, we found that phonemic awareness skills provided us with an unexpected result: we obtained averages of accurate phoneme identification and counting activities only in the 2nd grade of primary schools. For all children in Infantil IV, V, 1st grade and 7% of children in 2nd grade, the smallest unit of the word is the syllable. This statement is not affirmative only for words that begin with vocal phonemes, but when we asked the children to identify the beginning phonemes of words that begin with consonantal phonemes, most of the answers were the syllable, except for 2nd grade children. Children in the first three years of school analyzed had no explicit phonological development in seven analyzed skills. They could only identify letters. In the supraphonemic consciousness group, we achieved different and expressive results compared to the first type of consciousness. We noticed that children already present this type of consciousness in an explicit way in Early Childhood Education (Children IV and Children V). The most difficult task for children in this group was the fifth ability to produce words according to the conventions of the language. Of all the skills, those which children have most developed are rhyming. Identifying and counting syllables is also a skill which children have shown to master. The tasks which asked the children to count the word syllables represented one of the simplest, the hit rate was over 60% in the four school years. The writing of words was a skill which the children did not find very easy.